Environmental Suitability Modeling and Climate Change Implications for the Distribution of Pseudotsuga Menziesii (Mirb.) Franco for Mexico - Rodríguez-Ruiz, Rodolfo (2024)
[Introduction] Pseudotsuga menziesii (Mirb.) Franco is a forest species of great importance for its ecosystem services and commercialization. Currently, it has been documented that climate change is affecting populations in the north of the continent; however, how these changes will affect the distribution of the species in the future has not been assessed. [Objective] This study aimed to model the environmental suitability and potential distribution of P. menziesii over three periods: 2040, 2060, and 2080. [Methodology] First, environmental suitability and potential distribution were estimated based on records and bioclimatic variables with the help of MaxEnt. Then, transfers were made to two scenarios of carbon emissions in three periods. Finally, the loss of extension and decrease of environmental suitability were evaluated as a percentage. [Results] P. menziesii has a current potential distribution of 164,110 km2. The areas with the highest environmental suitability (> 0.5) were located in the north of the country, specifically in the states of the north. However, under the climate change scenarios, these zones suffered a greater decrease in their environmental suitability of > 50%, and a reduction in their extension of between 50.7% and 92.6%. In contrast, the most resilient populations to climate change were those in the south. [Conclusions] Pseudotsuga menziesii is favored by low temperatures; due to this, a drastic reduction in its potential distribution is expected. Coupled with this, environmental suitability will drop to more than 50% in the northern regions of the country. With a drastic loss of the area, the prevalence of the species could be at a point of decline.